Challenges in financing public sector low-carbon initiatives: lessons from private finance for a school district in British Columbia, Canada. (9th August 2018) - Jensen, Thor; Dowlatabadi, Hadi
ABSTRACT: Governments are major investors in climate change mitigation, but aversion to public indebtedness has led to reliance on private finance to deliver public assets. Compounding this challenge, financing through Energy Service Contracts is ruled out by accounting rules. With public and traditional private funding avenues closed, government departments have sought contracts that do not disclose the full cost of borrowing, such as the Public–Private Partnership (PPP) described in this case study. We unpack the utility contract filed with the provincial regulator to show that circumventing budgetary constraints cost the Delta School Board (DSB) 8.75% per annum on borrowed private funds while public finance would have cost 4%pa. All levels of the public sector are keen to play their role in climate mitigation. Climate policy is about not passing our burden of unbridled fossil fuel use and greenhouse gas emissions to future generations. If we do not exempt public sector capital investments for decarbonization from deficit regulations, we risk passing an unnecessary economic burden to future generations. Key policy insights Transition to a low-carbon economy requires public sector investments that exceed budget deficit regulations and political aversion in many jurisdictions; Private–Public Partnerships are currently viewed as the solution to this self-imposed fiscal constraint; PPPs without clear performance targets or contractual templates will expose less experienced public sector investors to high costs and emissions above expectations.